Design and simulation of rectangular patch microstrip antenna with inset feed for ADS-B system - Muttaqin Hardiwansyah; Dian Neipa Purnamasari (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The ADS-B system serves to track the location of aircraft. Ground station in the ADSB system is a receiver system that captures aircraft location signals using frequency 1090. Antenna is a key device for ADS-B communication. This paper is intended to develop a square microstrip antenna that has a working frequency of 1090 MHz. The material used is FR4 substrate, and the dielectric material is chopper. The antenna design is simulated using Matlab's Antenna Toolbox with its various conveniences. The simulation results of the patch antenna design with inset feed optimization resulted in a working frequency close to 1090 MHz, a VSWR value close to 1 and a Gain of 9.59 dBi.